Socioeconomic impact of innovative development of small and medium-sized enterprises on the post-war communities of Ukraine - Iaroslav Petrunenko; Volodymyr Ustymenko; Ruslan Dzhabrailov; Kristina Vozniakovska; Stanislav Sieriebriak (Heritage and Sustainable Development)
This study explores the socioeconomic impact of small and medium-sized enterprises (SMEs) on post-war communities in Ukraine, focusing on employment, income growth, poverty reduction, and community resilience. The research uses Bayesian simulation analysis to model various policy scenarios, including SME growth rates, innovation adoption, capital investment, and government support. Bayesian methods allow for flexible analysis, incorporating prior data and handling the uncertainty typical of post-war environments. The findings indicate that SME growth and innovation adoption significantly contribute to employment and income generation, with a 20% increase in SME growth leading to a 12% rise in employment and a 10% increase in household income. Capital investment proved to be the most influential factor. At the same time, government support plays a crucial role in reducing poverty and improving community resilience, with a 30% increase in government support resulting in a 5% reduction in poverty. The study concludes that targeted financial support, fostering innovation ecosystems, and robust government policies are essential to maximizing the socioeconomic contributions of SMEs in post-war Ukraine. These findings provide critical insights for policymakers to design effective strategies for economic recovery.